2020
DOI: 10.1063/5.0026552
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics and azimuthal behavior of the self-excited acoustic modes in axisymmetric shallow cavities

Abstract: Self-excitation of acoustic resonance in axisymmetric cavities can lead to a complex flow–acoustic coupling, which may result in severe noise generation. In this work, a large eddy simulation is performed to model the different flow–sound coupling mechanisms during the self-excitation of various excitable acoustic modes in an axisymmetric shallow cavity configuration with an aspect ratio of L/d = 1 over the lock-in region. The compressible Navier–Stokes equations are solved at a resolution sufficient to captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…2023 b ). These observations were corroborated through phase-locked particle image velocimetry (PIV) measurements (Ziada, Bolduc & Lafon 2017) and high-fidelity LES simulations (Abdelmwgoud, Shaaban & Mohany 2020; Wang et al . 2020).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…2023 b ). These observations were corroborated through phase-locked particle image velocimetry (PIV) measurements (Ziada, Bolduc & Lafon 2017) and high-fidelity LES simulations (Abdelmwgoud, Shaaban & Mohany 2020; Wang et al . 2020).…”
Section: Introductionmentioning
confidence: 73%
“…Due to the special azimuthal characteristics of the diametral acoustic mode, the interactive shear layers demonstrate an intensified three-dimensionality and even a spinning rotation behaviour (Faure-Beaulieu, Pedergnana & Noiray 2023a;Faure-Beaulieu et al 2023b). These observations were corroborated through phase-locked particle image velocimetry (PIV) measurements (Ziada, Bolduc & Lafon 2017) and high-fidelity LES simulations (Abdelmwgoud, Shaaban & Mohany 2020;Wang et al 2020). As for the depth-oriented acoustic mode, the direction of its acoustic particle velocity is generally perpendicular to that the streamwise-transported shear layer.…”
Section: Introductionmentioning
confidence: 78%
“…Nakiboğlu, Manders & Hirschberg (2012) used Howe's vortex sound theory (Howe 2002) and simulations of the incompressible unsteady Reynolds-averaged Navier–Stokes (RANS) equations of a harmonically forced axisymmetric cavity to predict at which forcing frequency the peak whistling is maximal, depending on the mean flow profile in the pipe and the cavity's aspect ratio. Compressible large eddy simulations (LES) by Wang & Liu (2020) and Abdelmwgoud, Shaaban & Mohany (2020) allowed them to identify the structure of the hydrodynamic fluctuations associated to standing and spinning aeroacoustic modes in axisymmetric cavities. The latter study revealed different vorticity patterns associated with standing and spinning modes.…”
Section: Introductionmentioning
confidence: 99%
“…2021), and also in the case of axisymmetric cavities (e.g. Aly & Ziada 2010; Nakiboğlu, Manders & Hirschberg 2012; Oshkai & Barannyk 2013; Abdelmwgoud, Shaaban & Mohany 2020; Wang & Liu 2020). In the latter situations, and when the cavity is deep, as in the present work, the first azimuthal acoustic modes are often involved.…”
Section: Introductionmentioning
confidence: 99%
“…These azimuthal aeroacoustic instabilities can be a critical problem in the design of piping systems, valves, turbomachines, boilers or heat exchangers. Moreover, they exhibit strong similarities to thermoacoustic instabilities in annular and axisymmetric combustors, where the driving mechanism originates from the unsteady heat release rate of the flames instead of the unsteady vorticity: in both types of systems, high-amplitude azimuthal oscillations can develop in the form of spinning, standing, mixed or beating acoustic waves (see for instance the papers from Aly & Ziada 2011;Abdelmwgoud et al 2020;Faure-Beaulieu et al 2021;Indlekofer et al 2021).…”
Section: Introductionmentioning
confidence: 99%